Energy audit of subcritical plant performance with different types of subbituminous coal - A. A., Nuraini; S., Salmi; A. A., Hairuddin (Zibeline International Publishing, 2019)
The energy used and energy waste are calculating accordingly and presented to the financial terms. Having said that, the energy audit is the activities of measuring the energy is being consumed and it also tells how efficiently and effectively the energy is being used. In addition, the energy audit critically identifies various weak at the field and becomes as a tools to inform the system to make and corrective actions, mitigation plant and the meantime monitor the performance. For this study, many parameters and calculation involved in an energy audit such as superheated steam temperature, superheated steam pressure, boiler drum level and other for the subcritical plant. For the condenser vacuum and condenser pressure, result shows within acceptance range which is between 65 to 95 bar. Besides that, the generator performance which indicate through generator active power and generator frequency, Hertz for all type of coal shows similar result which is within acceptable range. As a results, coal types D behave similar performance compare with designed coal type A. Overall, the energy audit gives very good assessment and valuable information on the plant performance and consequently depicts the plant life cycle.